The power of e-recruitment and employer branding on Indonesian millennials’ intention to apply for a job - Wijaya, Cindy Natalia; Mustika, Martina Dwi; Bulut, Sefa; Bukhori, Baidi (Frontiers in Psychology, 2023)
Companies need reliable employees to support their business. As e-grocery businesses in Indonesia continue to grow during the pandemic, various strategies are required to attract millennials. This study examined the effects of e-recruitment, employer branding, and employee value proposition methods (radical flexibility, deeper connection, personal growth, and holistic well-being) to increase millennial job applications in e-grocery companies in Indonesia. Using the experimental vignette method, we conducted three studies with a total of 619 millennial participants, who were recruited using the convenience sampling technique. All participants received a set of job advertisements as a stimulus. The results showed that e-recruitment could not significantly predict the millennials’ intentions when applying for jobs in e-grocery companies. Companies in Indonesia may need to analyze millennials’ familiarity with e-recruitment platforms, especially on company websites. However, employer branding successfully predicted millennials’ intention to apply for a job in e-grocery companies, which was not affected by the length of their work experience. Employer branding serves as a means of building job seekers’ trust through personal promotions. With this trust, job seekers are more motivated to apply to the company. When e-recruitment and employer branding were analyzed simultaneously, there were significant interactive effects on millennials’ intentions. Employer branding acted as a socialization medium to introduce e-recruitment and vice versa. E-recruitment served as a form of branding that could shape the perceptions and experiences of millennial job seekers. Lastly, the employee value proposition significantly predicted millennials’ intentions, where holistic well-being was the most sought-after value. It can support employees’ well-being and encourage them to make valuable propositions that will make e-grocery companies excel in Indonesian labor market.